Impact of extraction condition on the yield and molecular characteristics of collagen from Asian bullfrog (Rana tigerina) skin - Sylvia Indriani; Soottawat Benjakul; Hideki Kishimura; Supatra Karnjanapratum; Sitthipong Nalinanon (My University, 2022)
The present study is the first report on collagen extraction as acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC), which could maximize the exploitation of Asian bullfrog (Rana tigerina) skin as an alternative collagen material in food and pharmaceutical fields. Extraction methods for ASC and PSC from Asian bullfrog skin were developed using different concentrations of acetic acid (0.50, 0.75, and 1.00 M) and pepsin (1.00, 2.00, and 3.00% [w/w]). PSCs exhibited a higher extraction yield (22.59%–28.30%) and recovery (22.48%–31.12%) than ASCs. An electrophoretic study revealed that collagens possessed type I collagen. ASC with 0.75 M acetic acid (ASC-0.75) and PSC with 3.00% (w/w) pepsin (PSC-3.00) were selected and analysed on their solubility, molecular characteristics, and amino acid composition. A better solubility with a higher isoelectric point was observed for PSC-3.00 than ASC-0.75. Fourier transform infrared- and circular dichroism-spectra revealed a high-interacted compact structure with a triple helical-structure of the collagen peptides, respectively. A similar amino acid profile with a high imino acid content was observed. Therefore, collagens from Asian bullfrog skin were successfully extracted, where the optimized conditions provided a high yield with less adverse effects on collagen properties and molecular characteristics.
Keywords: Pepsin; Imino acid; Collagen: Extraction and Characterization